TECHNICAL ASSESSMENT OF EXPERTISE IN OPERATIONS MANAGEMENT, TECHNICAL INNOVATION, AND STRATEGIC LEADERSHIP - Chiaravalloti Gomes, Kauê (Humanas em Perspectiva, 2026)
This technical report assesses the expertise of Mr. Kauê Chiaravalloti Gomes, a professional of extraordinary ability in operations management, technical innovation, and strategic leadership. The methodology involved the analysis of documentary evidence, focusing on the technical manual he authored on the application of the ABNT NBR 16612 standard (GOMES, 2022). The report details his leadership in creating the first photovoltaic (TOX) cable with 100% national polymer, breaking the dependence on imported materials. The results demonstrate a profound sector-wide impact: a 23% cost reduction, a 40% decrease in lead time, and revenue of R$3 million over three years, with validated application in 108 MWp of solar plants (ABILITY/INMETRO, 2020). The innovation set a new market standard, adopted by multiple manufacturers. The assessment confirms an expertise that integrates engineering, management, and strategy, resulting in industrial transformation with measurable and lasting impact.